Dependence of posthypertonic hemolysis of initial state of canine erythrocytes - Chabanenko, Olena; Yershova, Natalia; Shpakova, Nataliia (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):239